Current and Future Point-of-Care Tests for Emerging and New Respiratory Viruses and Future Perspectives - Nelson, Philipp P. (Front Cell Infect Microbiol, 2020)
The availability of pathogen-specific treatment options for respiratory tract infections (RTIs) increased the need for rapid diagnostic tests. Besides, retrospective studies, improved lab-based detection methods and the intensified search for new viruses since the beginning of the twenty-first century led to the discovery of several novel respiratory viruses. Among them are human bocavirus (HBoV), human coronaviruses (HCoV-HKU1, -NL63), human metapneumovirus (HMPV), rhinovirus type C (RV-C), and human polyomaviruses (KIPyV, WUPyV). Additionally, new viruses like SARS coronavirus (SARS-CoV), MERS coronavirus (MERS-CoV), novel strains of influenza virus A and B, and (most recently) SARS coronavirus 2 (SARS-CoV-2) have emerged. Although clinical presentation may be similar among different viruses, associated symptoms may range from a mild cold to a severe respiratory illness, and thus require a fast and reliable diagnosis. The increasing number of commercially available rapid point-of-care tests (POCTs) for respiratory viruses illustrates both the need for this kind of tests but also the problem, i.e., that the majority of such assays has significant limitations. In this review, we summarize recently published characteristics of POCTs and discuss their implications for the treatment of RTIs. The second key aspect of this work is a description of new and innovative diagnostic techniques, ranging from biosensors to novel portable and current lab-based nucleic acid amplification methods with the potential future use in point-of-care settings. While prototypes for some methods already exist, other ideas are still experimental, but all of them give an outlook of what can be expected as the next generation of POCTs.